Velocity-sensitised Magnetic Resonance Imaging of foams - Bos, Kevin J.; Wilson, K. Gordon; Newling, Benedict (Diffusion Fundamentals, 2013)
Although flowing foams are used in a variety of technologies, foam rheology is still incompletely understood. In this paper we demonstrate the use of a velocity-sensitised magnetic resonance imaging (MRI) sequence for the study of flowing foam. We employ a constant-time (pure phase encode) imaging technique, SPRITE, which is immune to geometrical distortions caused by the foam-induced magnetic field inhomogeneity. The sample magnetisation is prepared before the SPRITE imaging with the Cotts 13-interval motion-sensitisation sequence, which is also insensitive to the effects of the foam heterogeneity. We measure the development of a power-law velocity profile in the foam downstream of a Venturi constriction (in which the cross-section of the tube decreases by 89% in area) in a vertical, cylindrical pipe.